Pengaruh Penggunaan Metode Reading Questioning and Answering (RQA) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Sejarah Kelas XI IIS di SMA N 3 Padang - Resi Ramadanis Arwis; Meldawati Meldawati; Zulfa Zulfa (Program Studi Pendidikan Sejarah Universitas Riau, 2021)
This study looked at the effect of using the Reading Questioning and Answering (RQA) method on student learning outcomes in history learning in class XI IIS at SMA Negeri Padang. Based on the results of processed research data with a predetermined formula and the help of Microsoft Excel, it was found that the results showed that there was an effect of the reading, questioning, and answering (RQA) method on the history learning outcomes of class XI IIS students at SMA Negeri 3 Padang. Learning with the Reading, Questioning, and Answering (RQA) method is good for the learning process because with the Reading Questioning and Answering (RQA) strategy learning method students participate actively in the learning process and make students more serious in reading and understanding the reading content, and find concepts about the material being studied. In addition, the presence of students making questions and answering these questions themselves can strengthen students' cognitive abilities and can empower their thinking skills deliberately. And through the independent application of this method by making questions and answers individually, students are more competent in a sporting way to get awards. Meanwhile, the application of the Reading Questioning and Answering (RQA) method with a system of dividing students into several groups can foster a system of cooperation and social attitudes among students in doing the assignments given by the teacher. The results of this study are very important because there is an influence from each variable, namely between the independent variable and the dependent variable.